Pengaruh Brand Image, Harga, Promosi, Dan Kualitas Produk Terhadap Keputusan Pembelian Kartu Pascabayar Indosat Di Semarang - Rasyad, Galih Bahrul Allam; Ikasari, Hertiana (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Contemporary information and technology has progressed at a rapid pace. More sophisticated, user-friendly and reasonably priced communication technologies are in high demand due to their ease of use from a business standpoint. As the need for internet services in Indonesia continues to increase, several operators provide internet cards or quotas at different prices. The operator in question is Indosat. The purpose of this study is as a way to test Brand image, Price, Promotion, and Product Quality on Purchasing Decisions for Indosat postpaid cards in Semarang City. The method used in this research is quantitative. The method for obtaining samples using purposive sampling techniques uses 120 respondents by distributing questionnaires via google form. The data analysis process uses SPSS, and the data analysis tool uses multiple linear regression. The results of data processing state that brand image and product quality have no significant effect on purchasing decisions while price and promotion have a significant influence on purchasing decisions for Indosat postpaid cards in Semarang. Keywords: Brand Image, Price, Promotion, Product Quality, Purchase Decision